A comparative study between epidural butorphanol with bupivacaine and bupivacaine alone for intra-operative and post-operative analgesia in lower limb orthopaedic surgeries - Kar, Prachi (International Journal of Research in Medical Sciences, 2016)
Background: Addition of opioids to epidural local anaesthetic improves the onset and duration of analgesia. The present study was conducted to evaluate the safety and efficacy of addition of various doses of butorphanol to epidural bupivacaine. Methods: After taking written informed consent, 100 American society of anesthesiologist (ASA) grade I and II patients of both gender and age between 20-50 years undergoing elective lower limb orthopedic surgery under epidural anaesthesia were recruited for the study. Epidural space was identified by standard technique and catheter was left in place. The patients were randomly divided into 4 groups: group-1- Bupivacaine 0.5% 16ml, group-II- bupivacaine 0.5% 16ml+1mg butorphanol, group-III- Bupivacaine 0.5% 16ml+2mg butorphanol, group-IV-bupivacaine 0.5% 16ml+4mg butorphanol. The final volume was made 18ml by addition of normal saline. hemodynamic parameters, various block characters like onset and duration of sensory block, quality of analgesia, quality of motor block, and side effects were noted. Data were compared using chi square test and ANOVA test with post-hoc analysis. Results: The time to onset of sensory block was significantly lesser in patients receiving 2 and 4 mg butorphanol. The duration of analgesia was significantly prolonged in all the groups receiving butorphanol. There were no serious cardiorespiratory side effects. Incidence of sedation was higher in Group II and IV patients but there was no respiratory depression. Conclusions: we conclude that butorphanol 2 mg and 4 mg can be used as safe and effective adjuvant to epidural bupivacaine in patients undergoing lower limb orthopedic surgeries.